Cocoa Farmers’ Participation in Farmers Business Schools Activities in Osun State, Nigeria - Badiru, Idris Olabode; Ladigbolu, Temitope Adejoju; Arogundade, John Oshukunofa (Journal of Agricultural Extension, 2023)
This study assessed cocoa farmers’ participation in FBS activities in Osun State, Nigeria. A three-stage sampling procedure was used to select 131 cocoa farmers. Information on respondents’ participation, knowledge, satisfaction, benefits and constraints to participating in FBS activities were collected through the interview schedule. Data gathered were analysed using mean, standard deviation, Weighted Score (WS) and Pearson Product Moment Correlation (PPMC) at α0.05. Cocoa farmers’ farm size and years of farming experience were 3.82±5.71 and 21.50±13.61 respectively. They participated in classroom work and discussion (WS=156.5), benefited from improved knowledge of farm management and farm record (¯x=1.00) and were satisfied with the training schedule fixing (WS=150.3). However, they were constrained by inadequate funds to use the knowledge acquired (WS=139.8). Respondents had a high level of participation (51.9%), knowledge (55.0%) and satisfaction (50.4%) about FBS activities. Significant relationships existed among respondents’ participation (r=0.041), satisfaction (r=0.321) and knowledge about FBS activities. Farmers’ participation in the FBS improved their knowledge of farm business management hence, should be continued to impact their livelihoods.